Withdrawal Of Draft Regional Regulations By Regional Heads Before The Process Of Discussing The Draft Regional Regulations - Eka NAM Sihombing; Cynthia Hadita (Veteran Law Review, 2022)
The problem of withdrawing the draft local regulations before the discussion process by the Regional Head occurs in the process of forming local regulations. The research method used is normative juridical. The purpose of this research is to answer the problem of withdrawing the draft local regulations before the discussion process by the Regional Head occurs in the process of forming local regulations in aspects of legislation. The results showed that there were still many draft local regulations that were withdrawn before the process of discussing the Local regulation Draft conducted by the Regional Head. Supposedly, the process of its formation applies mutatis mutandis with the formation of legislation, if it has entered the discussion process then it cannot be retracted, as is the practice in the Philippines, there must be parameters if the draft local regulation must be withdrawn before discussion and also its legitimacy must be contained in the Local Government Law.